A new analytical solution for cure-induced spring-in of L-shaped composite parts. (8th February 2019) - Ding, Anxin; Wang, Jihui; Ni, Aiqing; Li, Shuxin
Abstract: A new analytical solution for the prediction of cure-induced spring-in of L-shaped composite parts has been proposed based on modification of the model presented by authors (2017). In the newly proposed analytical solution, the flange length is incorporated into the formulation to theoretically derive the spring-in of corner of L-shaped composite part using shear-lag theory. Consequently, in addition to the cure process generated non-mechanical strain in the rubbery state in the through-thickness and length directions, the new solution can quantitatively give the correlation of spring-in of corner of L-shaped composite part with the flange length. Then, the newly proposed analytical solution is verified by the good agreement between the analytically calculated and experimentally measured spring-in angles for both the unidirectional and cross-ply L-shaped composite parts. Further numerical simulation on the elaborately selected L-shaped composite parts with various configurations also provides a favourable comparison with analytical results, showing the validity of newly proposed analytical solution.